Helicopsyche (Feropsyche) timbira sp. nov. (Trichoptera: Helicopsychidae), a new species from southeastern Brazil - Da Silva, André Luiz Ramos; Santos, Allan Paulo Moreira; Nessimian, Jorge Luiz (Zootaxa, 2014)
The family Helicopsychidae comprises only two genera, the monotypic Rakiura McFarlane 1973 and the diverse Helicopsyche von Siebold 1856. Johanson (1998) provided a phylogenetic and biogeographic analysis for Helicopsyche, and ranked all other previously Helicopsychidae genera as subgenera of Helicopsyche. Currently, Helicopsyche is subdivided into six subgenera: Helicopsyche, Petrotrichia Ulmer 1910, Galeopsyche Johanson 1998, Saetotrichia Brauer 1865, Cochliopsyche Müller 1885, and Feropsyche Johanson 1998. Johanson (2002, 2003) provided revisions to Neotropical species of Helicopsyche. These species belong to the subgenus Cochliopsyche (currently with 16 species) or to the subgenus Feropsyche (with about 100 species), both endemic to the Neotropics. According to Johanson & Malm (2006), the Neotropical fauna can be divided into three regions: One that includes the West Indies, where 33 Helicopsyche species are recorded, another including Central America, with 25 Helicopsyche species, and finally, another one that includes South America, with 41 Helicopsyche species. In Brazil, only 19 species are recorded, of which six are from the southeastern region (Santos et al. 2013). However, the Brazilian fauna is underestimated and possibly much richer than these numbers indicate, especially when it is compared to regions of Central America or South America, such as Venezuela (28 spp.) and Mexico (18 spp.) (Johanson & Malm 2006). In this work, a new species of Helicopsyche (Feropsyche) is described from southeastern Brazil. Specimens were collected at Serra dos Órgãos (Rio de Janeiro State), a mountain range that includes a large remnant of the Atlantic Forest in Brazil. Additional specimens were identified from São Paulo State, in an area that, along with the Serra dos Órgãos, is a part of the forest corridor of the mountain range named Serra do Mar.